1989
DOI: 10.1042/bj2640447
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil degranulation inhibits potential hydroxyl-radical formation. Relative impact of myeloperoxidase and lactoferrin release on hydroxyl-radical production by iron-supplemented neutrophils assessed by spin-trapping techniques

Abstract: Hydroxyl radical ('OH) formation by neutrophils in vitro requires exogenous iron. Two recent studies [Britigan, Rosen, Thompson, Chai & Cohen (1986) J. Biol. Chem. 261, 17026-17032;Winterbourn (1987) J. Clin. Invest. 78, 545-550] both reported that neutrophil degranulation could potentially inhibit the formation of OH, but differed in their conclusions as to the responsible factor, myeloperoxidase (MPO) or lactoferrin (LF). By using a previously developed spin-trapping system which allows specific on-line dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 68 publications
0
18
1
Order By: Relevance
“…And it had been shown in experiments that anti-lactoferrin antibodies could increase both the magnitude and duration of hydroxyl radical formation [22]. Therefore, we speculated that ANCA specific to antigens, other than MPO and PR3, might also involve in the pathogenesis of AASV.…”
Section: Discussionmentioning
confidence: 97%
“…And it had been shown in experiments that anti-lactoferrin antibodies could increase both the magnitude and duration of hydroxyl radical formation [22]. Therefore, we speculated that ANCA specific to antigens, other than MPO and PR3, might also involve in the pathogenesis of AASV.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have found that at least two of the granular components affect the potential for * OH formation in association with the neutrophil respiratory burst. Lactoferrin and myeloperoxidase inhibit * OH formation by iron-supplemented neutrophils by sequestering iron in a noncatalytic form and consuming H202, respectively (15,20,54). In contrast, it seemed possible that neutrophil proteases through their action on the peptide PVD could alter the potential of iron bound to PVD to participate in the Haber-Weiss reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Since peritoneal cells (macrophages) lack MPO, the cytotoxicity of H,O~ is mainly increased by the generation of hydroxyl radical [30]. Free radical damage in biological systems is largely attributed to OH" generation [8]; however, the capacity to form hydroxyl radical in significant concentrations has recently been questioned [2]. In this report we show that hydroxyl radical is implicated in the killing of C neoJbrmans by rat PC demonstrated by the fact that killing of C neofornlans was effectively inhibited by benzoate, a reagent scavenger of hydroxyl radical (Fig.…”
Section: Discussionmentioning
confidence: 99%